Association between Obesity and Dental Caries among Young Population Presenting at Tertiary Care Hospital : Association Between Obesity and Dental Caries - Khatoon, Reshma; Bughio, Rashid Iqbal; Memon, Khalida Naz; Memon, Sikandar Munir; Soomro, Zaheer Ahmed; Kandhro, Rehmatullah (Pakistan Journal of Health Sciences, 2023)
Globally, dental caries and obesity are becoming issue of public health concern. There are inconsistent and contrasting results drawn from numerous studies seeking the association between obesity and dental caries. Objective: To ascertain the relationship between childhood obesity and dental caries at a tertiary care hospital. Methods: A cross-sectional descriptive research was carried out at department of dentistry of LUMHS hospital Jamshoro/Hyderabad.161 obese patients aged 18 to 35 years of both genders having BMI ≥ 25kg/m2 were selected by convenience sampling technique. After taking detailed history, clinical examination of mouth of each patient was performed by using mouth mirror and probe. Dental caries was recorded according to the WHO criteria using decayed, missing, and filled teeth (DMFT) index and the G. V. Black classification, while height and weight was measured using BMI index. All data were recorded in standard proforma for analysis by using SPSS version 23.0. Results: There was male preponderance i.e. 86 (53.42%) males as compared to 75 (46.58%) females. Themeanagerecordedwas25.7 ± 6.1 years. Majority of the subjects were belonged to rural areas (91.30%). THEMEAN and standard deviation of BMI was29.0 ± 3.1 (25.0-40.7) Kg/m2. The mean and standard deviation of DMFT score was 0.57 ± 1.0 with the range of 0-4. Dental caries was present in 45 (27.95%) patients and absent in 116 (72.05%) presents. The highly significant association was observed between high BMI AND dental caries (p< 0.001). Conclusions: Dental caries and obesity are significantly associated among young population. As the obesity level increased, risk of dental caries can also be increased.